2021
DOI: 10.1002/brb3.2065
|View full text |Cite
|
Sign up to set email alerts
|

Parcellation‐based anatomic model of the semantic network

Abstract: Introduction The semantic network is an important mediator of language, enabling both speech production and the comprehension of multimodal stimuli. A major challenge in the field of neurosurgery is preventing semantic deficits. Multiple cortical areas have been linked to semantic processing, though knowledge of network connectivity has lacked anatomic specificity. Using attentional task‐based fMRI studies, we built a neuroanatomical model of this network. Methods One hundred and fifty‐five task‐based fMRI stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…Therefore, affective functions may constitute an important factor of DMN reorganization during task execution. We also note that PC2 and IC2 (but PC1 as well) resemble the SemN (Noonan et al 2013;Chiou et al 2020;Evans et al 2020;Milton et al 2021). Furthermore, they remind the transitional module serving an integrative function with FPN observed by Fornito et al (2012), as well as with the Overlapping Community six found by Najafi et al (2016).…”
Section: Discussionsupporting
confidence: 60%
“…Therefore, affective functions may constitute an important factor of DMN reorganization during task execution. We also note that PC2 and IC2 (but PC1 as well) resemble the SemN (Noonan et al 2013;Chiou et al 2020;Evans et al 2020;Milton et al 2021). Furthermore, they remind the transitional module serving an integrative function with FPN observed by Fornito et al (2012), as well as with the Overlapping Community six found by Najafi et al (2016).…”
Section: Discussionsupporting
confidence: 60%
“…By including reported stereotactic coordinates from previous studies, more anatomically precise results can be obtained. In this context, we have been attempting to characterize all of our current findings within the HCP nomenclature given its more precise parcellation scheme (Kuiper et al., 2020 ; Milton et al., 2021 ; Sandhu et al., 2021 ; Sheets, Briggs, Dadario, et al., 2021 ). For instance, the anterior cingulate cortex and insula are known to be functionally divided within numerous subdivisions (Glasser et al., 2016 ), yet previous studies on the SN network continue to generally reference these regions as just general nodes in the SN.…”
Section: Discussionmentioning
confidence: 99%
“…By utilizing coordinate‐based methodology, one can overcome the heterogeneous topographical nomenclature often described in the literature for homologous brain regions. This methodology has allowed us to precisely characterize many other brain networks in great detail, such as the default mode network (DMN); however, it has not been applied in a similar context for the SN to date and therefore remains a potentially advantageous avenue worth exploring (Milton et al., 2021 ; Poologaindran et al., 2020 ; Sandhu et al., 2021 ; Sheets, Briggs, Dadario, et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, pars triangularis was the most robustly-identified hub and was the only node to appear as part of the ISN in every participant, suggesting a common functional role across individuals. Parts of left IFG, particularly pars triangularis, have been previously described as both a functional and structural hub possibly involved in cognitive control due to its density of connections to medial prefrontal cortex (Milton et al, 2021; Vandenberghe et al, 2013; Xu et al, 2016). Further, rTMS experiments have shown that disruption of anterior IFG is associated with increased latency on semantic but not phonological tasks (Gough et al, 2005; Klaus & Hartwigsen, 2019; Whitney et al, 2010), supporting its role as a critical node in the semantic network.…”
Section: Discussionmentioning
confidence: 99%